A Laboratory Methodology for Dual RNA-Sequencing of Bacteria and their Host Cells In Vitro - Marsh, James W.; Humphrys, Michael S.; Myers, Garry S. A. (Frontiers in Microbiology, 2017)
Dual RNA-Sequencing leverages established next-generation sequencing (NGS)-enabled RNA-Seq approaches to measure genome-wide transcriptional changes of both an infecting bacteria and host cells. By simultaneously investigating both organisms from the same biological sample, dual RNA-Seq can provide unique insight into bacterial infection processes and reciprocal host responses at once. However, the difficulties involved in handling both prokaryotic and eukaryotic material require distinct, optimized procedures. We previously developed and applied dual RNA-Seq to measure prokaryotic and eukaryotic expression profiles of human cells infected with bacteria, using in vitro Chlamydia-infected epithelial cells as proof of principle. Here we provide a detailed laboratory protocol for in vitro dual RNA-Seq that is readily adaptable to any host-bacteria system of interest.